PENOLAKAN TIONGKOK TERKAIT PENGAJUAN KEANGGOTAAN INDIA DALAM NUCLEAR SUPPLIERS GROUP (NSG) - Parama Nanda, I Made Widhi Sadhana; Priadarsini, Ni Wayan Rainy; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This research aims to explain why China opposes India’s membership in the Nuclear Suppliers Group (NSG) by using explanatory qualitative methods. India's desire to become a member of the NSG is based on India's fulfillment of clean energy and gaining international legitimacy as nuclear weapons countries. The submission of India membership is supported by a majority of NSG members including four countries from the P5 Countries. Although, many countries supported the submission of Indian membership, China decided to oppose, which make China the only P5 Countries that blocks India's membership in the NSG. This research uses the Neorealism framework to answer the reasons behind China's refusal on India’s membership in the NSG. The research then found the answer that China's rejection was based on China's efforts to protect its survival from threats from other countries while simultaneously maintaining a strategic balance in the South Asian region. Keywords: China, India, Neorealism, Nuclear Suppliers Group (NSG)